Menstrual Disorders and Work Stress: Psychosocial Hazards among Female Workers - Farahul Jannah; Ismi Farah Syarifah; Januar Ariyanto; Agung Raharjo; Moch. Sahri (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
The issues commonly faced by female workers are related to psychosocial hazards, which can lead to work stress among female workers. Unmanaged work stress can have negative effects on the health of female workers, one of which is menstrual disorders. This study aims to analyze the psychosocial hazards and the menstrual disorders frequently experienced by female workers. This research is a literature review, with Google Scholar used as the database for article searches. The literature search criteria in this study followed the PICOS approach. The results of this literature review indicate that work stress is associated with menstrual disorders in female workers. The most frequently reported stressor is workload, while the menstrual disorders experienced by female workers include premenstrual syndrome, dysmenorrhea, and abnormal menstrual cycles.